Microscopic State of Polymer Network Chains upon Swelling and Deformation - Naumova, Anna (2019)
We use low-resolution proton NMR to probe the chain deformation in swollen and nonlinearly deformed vulcanized rubber and end-linked PDMS networks on a microscopic level, extending earlier work focusing on uniaxial stretching and isotropic dilation upon swelling toward biaxial deformation and deformation of swollen samples. Previous studies have revealed that chain deformation in bulk samples is best described by tube models, and that chains in swollen samples deform affinely after an initial desinterspersion stage, upon which entanglement-related packing effects are relieved. We test whether a subsequent deformation may also be closer to affine, and find that this is not the case. Unexpectedly, nonisotropic deformation of swollen samples also follows tube-model predictions, which is explained by a dominance of structural inhomogeneities and significant reorganization of the topological constraints active in the swollen and possibly even the bulk state.